cal justification in Andalusian poetry: a study of selected historical and literary models - Sabreen Khalaf Hussein, Dr. (lark, 2026)
Occasional poetry refers to verses composed for specific events, whether personal, social, or political. Poets often represented as the voice of their societies both ancient, and modern ,providing them with a detailed history of their occasions.so we can say that the poetry of occasion specifically reflects the fluctuations of society and its political , social and religious events. The poet either writes poetry for his own free will , by force, or in response to an official assignment that requires saying , however the poet in many cases is hidden and behind what he has proven is a specific occasion, it’s difficult to reach the poet’s passions, orientations, visions , or emotional intensity in the poetry of the occasion..